2017
DOI: 10.1016/j.chembiol.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

General and Modular Strategy for Designing Potent, Selective, and Pharmacologically Compliant Inhibitors of Rhomboid Proteases

Abstract: SummaryRhomboid-family intramembrane proteases regulate important biological processes and have been associated with malaria, cancer, and Parkinson's disease. However, due to the lack of potent, selective, and pharmacologically compliant inhibitors, the wide therapeutic potential of rhomboids is currently untapped. Here, we bridge this gap by discovering that peptidyl α-ketoamides substituted at the ketoamide nitrogen by hydrophobic groups are potent rhomboid inhibitors active in the nanomolar range, surpassin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 74 publications
2
71
0
Order By: Relevance
“…Both endogenous and ectopically expressed YqgP cleaved endogenous MgtE, yielding distinct cleavage products (Fig A). The cleavage was abrogated by a rhomboid‐specific peptidyl ketoamide inhibitor (Ticha et al , ) at low nanomolar levels, confirming that it was a rhomboid‐specific event (Fig B). Judging by the apparent molecular size of the N‐terminal cleavage fragment compared with the in vitro ‐translated reference fragments (Lemberg & Martoglio, ) of MgtE, we concluded that the cleavage by YqgP occurred within the extracytoplasmic loop between TMH1 and TMH2 of MgtE.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…Both endogenous and ectopically expressed YqgP cleaved endogenous MgtE, yielding distinct cleavage products (Fig A). The cleavage was abrogated by a rhomboid‐specific peptidyl ketoamide inhibitor (Ticha et al , ) at low nanomolar levels, confirming that it was a rhomboid‐specific event (Fig B). Judging by the apparent molecular size of the N‐terminal cleavage fragment compared with the in vitro ‐translated reference fragments (Lemberg & Martoglio, ) of MgtE, we concluded that the cleavage by YqgP occurred within the extracytoplasmic loop between TMH1 and TMH2 of MgtE.…”
Section: Resultsmentioning
confidence: 56%
“…Bacillus subtilis genome encodes two rhomboid protease genes, ydcA and yqgP [also known as gluP (Mesak et al , )]. No proteolytic activity has been detected for YdcA so far (Urban et al , ; Lemberg et al , ), while YqgP is a commonly used model rhomboid protease cleaving a number of synthetic substrates (Lemberg et al , ; Urban & Wolfe, ; Ticha et al , ,b). YqgP has homologs in a number of Gram‐positive bacteria, including Bacilli, but also Staphylococci, Listeriae and others (http://www.ebi.ac.uk/interpro/protein/P54493/similar-proteins), and thus represents an attractive system to explore the cell biology and functions of bacterial rhomboid proteases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations